Targeted therapy with MXD3 siRNA, anti‐CD22 antibody and nanoparticles for precursor B‐cell acute lymphoblastic leukaemia. (8th September 2014) - Satake, Noriko; Duong, Connie; Chen, Cathy; Barisone, Gustavo A.; Diaz, Elva; Tuscano, Joseph; Rocke, David M.; Nolta, Jan; Nitin, Nitin
Summary Conventional chemotherapy for precursor B‐cell (preB) acute lymphoblastic leukaemia (ALL) has limitations that could be overcome by targeted therapy. Previously, we discovered a potential therapeutic molecular target, MDX3 (MAX dimerization protein 3), in preB ALL. In this study, we hypothesize that an effective siRNA therapy for preB ALL can be developed using antiCD22 antibody (αCD22 Ab) and nanoparticles. We composed nanocomplexes with super paramagnetic iron oxide nanoparticles (SPIO NPs), αCD22 Abs and MXD3 siRNA molecules based on physical interactions between the molecules. We demonstrated that the MXD3 siRNA‐αCD22 Ab‐SPIO NP complexes entered leukaemia cells and knocked down MXD3, leading the cells to undergo apoptosis and resulting in decreased live cell counts in the cell line Reh and in primary preB ALL samples in vitro. Furthermore, the cytotoxic effects of the MXD3 siRNA‐αCD22 Ab‐SPIO NP complexes were significantly enhanced by addition of the chemotherapy drugs vincristine or doxorubicin. We also ruled out potential cytotoxic effects of the MXD3 siRNA‐αCD22 Ab‐SPIO NP complexes on normal primary haematopoietic cells. Normal B cells were affected while CD34‐positive haematopoietic stem cells and non‐B cells were not. These data suggest that MXD3 siRNA‐αCD22 Ab‐SPIO NP complexes have the potential to be a new targeted therapy for preB ALL.